(untitled) (Texas Journal of Philology, Culture and History, 2024)
This article analyzes the railway that constructed by the Russian Empire in Turkestan, based on information from the newspaper “Turkestan Viloyatining Gazeti”. It reveals the importance of this railway, which was built by the imperial government to facilitate colonial governance in Turkestan and efficiently utilize the region’s economic resources. At the same time, the article provides information on the railway networks, the work processes involved in its construction, the number of people and goods transported after it was completed, as well as the economic hardships faced by the people of Turkestan.